2020
DOI: 10.5696/2156-9614-10.27.200905
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals in Vegetables and Associated Health Risks in Industrial Areas of Savar, Bangladesh

Abstract: Background. The occurrence of high levels of trace metals in foodstuffs represents a significant threat to human health. Vegetables grown in metal-contaminated soil or irrigated with wastewater can accumulate metals and bioaccumulate in the food chain affecting animals and humans. Objectives. The present study aimed to measure the levels of lead (Pb), cadmium (Cd), chromium (Cr) and cobalt (Co) in common vegetables grown in the industrial areas of Savar, Bangladesh, and to determine their potential health risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…All the THQ values for Pb were above 5, denoting that Pb may pose a major risk to the consumers. This finding is in an agreement with the findings of Amin et al, [27] The carcinogenic risk associated with the ingestion of studied vegetable species was evaluated by assessing target cancer risk (TR) and is presented in Table 4. The TR values ranged from 2.33E-04 to 5.30E-04 for Cd, 1.52E-4 to 2.11E-4 for Pb, 1.36E-02 to 1.85E-2 for Ni and 6.41E-4 to 1.17E-3 for Cr.…”
Section: Human Health Risk Assessmentsupporting
confidence: 90%
See 3 more Smart Citations
“…All the THQ values for Pb were above 5, denoting that Pb may pose a major risk to the consumers. This finding is in an agreement with the findings of Amin et al, [27] The carcinogenic risk associated with the ingestion of studied vegetable species was evaluated by assessing target cancer risk (TR) and is presented in Table 4. The TR values ranged from 2.33E-04 to 5.30E-04 for Cd, 1.52E-4 to 2.11E-4 for Pb, 1.36E-02 to 1.85E-2 for Ni and 6.41E-4 to 1.17E-3 for Cr.…”
Section: Human Health Risk Assessmentsupporting
confidence: 90%
“…The highest contributing metal in TR was found to be Ni among all three vegetable species. This high cancer risk is worse than the findings of Amin et al [27] where the values were less or equal to the threshold value of 10 -4 . This draws attention to a serious health concern for the inhabitants who are consuming the vegetables grown near the studied area.…”
Section: Human Health Risk Assessmentcontrasting
confidence: 71%
See 2 more Smart Citations
“…Emission of heavy metals from industries and vehicles may be deposited on vegetable surfaces during their production, transport and marketing. Recently, (Al Amin, at al.,2020) reported that atmospheric deposition can significantly elevate the levels of heavy metals contamination in vegetables commonly sold in the markets of ISSN: 2488-9229 FEDERAL UNIVERSITY GUSAU-NIGERIA Varanasi, India. The prolonged consumption of unsafe concentrations of heavy metals through foodstuffs may lead to the chronic accumulation of heavy metals in the kidney and liver of humans causing disruption of numerous biochemical processes, leading to cardiovascular, nervous, kidney and bone diseases (Klein-Junior et al, 2020).…”
Section: Introductionmentioning
confidence: 99%